Interface engineering in two-dimensional heterostructures towards novel emitters. (1st January 2023) - Li, Hua; Ling, Jinyang; Lin, Jiamin; Lu, Xin; Xu, Weigao
Abstract: Two-dimensional (2D) semiconductors have captured broad interest as light emitters, due to their unique excitonic effects. These layer-blocks can be integrated through van der Waals assembly, i.e., fabricating homo- or heterojunctions, which show novel emission properties caused by interface engineering. In this review, we will first give an overview of the basic strategies that have been employed in interface engineering, including changing components, adjusting interlayer gap, and tuning twist angle. By modifying the interfacial factors, novel emission properties of emerging excitons are unveiled and discussed. Generally, well-tailored interfacial energy transfer and charge transfer within a 2D heterostructure cause static modulation of the brightness of intralayer excitons. As a special case, dynamically correlated dual-color emission in weakly-coupled bilayers will be introduced, which originates from intermittent interlayer charge transfer. For homobilayers and type Ⅱ heterobilayers, interlayer excitons with electrons and holes residing in neighboring layers are another important topic in this review. Moreover, the overlap of two crystal lattices forms moiré patterns with a relatively large period, taking effect on intralayer and interlayer excitons. Particularly, theoretical and experimental progresses on spatially modulated moiré excitons with ultra-sharp linewidth and quantum emission properties will be highlighted. Moiré quantum emitter provides uniform and integratable arrays of single photon emitters that are previously inaccessible, which is essential in quantum many-body simulation and quantum information processing. Benefiting from the optically addressable spin and valley indices, 2D heterostructures have become an indispensable platform for investigating exciton physics, designing and integrating novel concept emitters.